1993
DOI: 10.1002/pros.2990220406
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural study of the ventral lobe of the prostate of rats submitted to experimental chronic alcoholism

Abstract: The effects of chronic alcohol ingestion on the ventral lobe of the prostate were studied in rats (Rattus norvegicus). Ultrastructural observations on the epithelial cells of the ventral lobe of the prostate showed irregularly shaped nuclei with deep infoldings, dilated RER cisternae, and a small number of microvilli covering the cell surface. After 90 and 135 days of alcohol treatment, the epithelial cells showed signs of degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0
6

Year Published

1996
1996
2007
2007

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 14 publications
4
15
0
6
Order By: Relevance
“…The authors observed cellular degenerative changes by electron microscopy, mainly dilatation in ER cisternae, huge Golgi complexes, lipid droplets, decrease in height and number of microvilli encircling the cellular surface and decrease in secretory activity. It was noted that long-lasting degeneration in the epithelium cells due to exposure to chronic alcohol causes a decrease in the cellular secretory activity [14]. However, the authors did not examine the possible change of the serum PSA levels [14].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The authors observed cellular degenerative changes by electron microscopy, mainly dilatation in ER cisternae, huge Golgi complexes, lipid droplets, decrease in height and number of microvilli encircling the cellular surface and decrease in secretory activity. It was noted that long-lasting degeneration in the epithelium cells due to exposure to chronic alcohol causes a decrease in the cellular secretory activity [14]. However, the authors did not examine the possible change of the serum PSA levels [14].…”
Section: Discussionmentioning
confidence: 91%
“…It was noted that long-lasting degeneration in the epithelium cells due to exposure to chronic alcohol causes a decrease in the cellular secretory activity [14]. However, the authors did not examine the possible change of the serum PSA levels [14]. We observed ultrastructural changes similar to the results of the study by Martinez et al in the cells of prostate tissue after acute alcohol intake, but we found that acute alcohol has an early effect (3 h) and that there was an increase in the serum level of PSA-like protein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Por consequencia, ocorre também a redução de estrógeno, uma vez que a aromatização hepática da testosterona é a única fonte fisiológica de estrógeno no organismo masculino (García-Flórez et al, 2005). Em estudo menos recente, Martinez et al (1993), avaliaram o efeito do alcoolismo crônico sobre a próstata de ratos, verificando modificações expressivas na atividade secretora e degeneração celular no epitélio glandular. Estes mesmos achados são observados após a orquiectomia, que promove a depleção de andrógenos e consequentemente atrofia da próstata em mais de 94% quando comparada aos animais controle (Antonioli et al, 2007 (Lieber, 2001;Paton, 2005;Gemma et al, 2006).…”
Section: Parâmetros Bioquímicosunclassified